Understanding of the life experience of homeless women - Biscotto, Priscilla Ribeiro; Jesus, Maria Cristina Pinto de; Silva, Marcelo Henrique da; Oliveira, Deíse Moura de; Merighi, Miriam Aparecida Barbosa (Revista da Escola de Enfermagem da USP, 2016)
To understand the life experience of homeless women. A social phenomenological study was conducted with 10 women assisted by a shelter. The analysis of the interviews was based on the theoretical framework of social phenomenology of Alfred Schütz and thematic literature. The participants face adversities in the street context, with emphasis on the risk of physical and sexual abuse, and seek shelters as a possibility for minimizing difficulties experienced. They hope to leave the streets; however, they see themselves trapped in this social reality, due to the addiction to alcohol and other drugs. The understanding of the life experience of homeless women shows daily confrontations and reveals the conflict between the desire for leaving and remaining on the streets, given the complexity of the reality that keeps them in this condition.

Comprender la vivencia de mujeres en situación de calle. Investigación fenomenológica social realizada con 10 mujeres asistidas por un albergue. El análisis de las entrevistas se ancló en el marco de referencia teórico de la fenomenología social de Alfred Schütz y la literatura temática. Las participantes enfrentan adversidades en el contexto de la calle, con énfasis para el riesgo de violencia física y sexual, y buscan el albergue como posibilidad de minimizar las dificultadas vividas. Ellas tienen como expectación salir de la calle, pero se ven presas a dicha realidad social en virtud de la adicción al alcohol y a otras drogas. La comprensión de la vivencia de mujeres en situación de calle señala enfrentamientos cotidianos y desvela el conflicto entre el deseo de salir y permanecer en la calle, en virtud de la complejidad de la realidad que las mantiene en dicha condición.
Keywords: Women; Homeless persons; Social vulnerability; Qualitative research